Immigration and Women in "Flight against Time" by Emily Nasrallah - Ali Ganjian Khenari; Hawra Rashnow (دراسات فی اللغه العربیه و آدابها)
Emily Nasrallah, with her tender feelings and profound thoughts, has directed our attention, in her works, towards social issues such as war, immigration and women affairs. The fact that modern man no longer holds to his spiritual values such as faith and love demonstrates how significant these social issues are. Emily Nasrallah emphasizes patriotism and resistance, because she believes these to be still important. In her novel "Flight against the Time", she discusses the merits and demerits of immigration and constantly compares homeland with Diaspora. These comparisons are based on human nature and conscience. It is natural that at the time of war any country needs its militants and soldiers. In Lebanon, however, large numbers of people migrated to other countries at the time of war which had unfortunate consequences including loss of identity. This Lebanese novelist has addressed these consequences. The present research aims at investigating the theme of "Flight against Time" with reference to women and immigration which are the two dominant themes of the novel. Moreover, it examines the life and character of the author. This paper utilizes a technical and psychological method as well as criticism and comparison.